Evidence That ADAM17 Mediates the Protective Action of CGRP against Angiotensin II-Induced Inflammation in Vascular Smooth Muscle Cells - Si-yu Zeng; Li Yang; Chen-liang Hong; Hui-qin Lu; Qiu-jiang Yan; Yan Chen; Xu-ping Qin (Hindawi Limited, 2018)
Calcitonin gene-related peptide (CGRP) has a potent protective action on the cardiovascular system; however, little is known about the role of CGRP in angiotensin II- (Ang II-) induced inflammation of vascular smooth muscle cells (VSMCs). This study is aimed at determining the anti-inflammatory effect of CGRP in Ang II-treated VSMCs and whether a disintegrin and metalloproteinase 17 (ADAM17) modulates this protective action. Small interference RNA (siRNA) and inhibitors of CGRP, epidermal growth factor receptor (EGFR), and extracellular signal-regulated kinase 1/2 (ERK1/2) were adopted to investigate their effect on Ang II-induced inflammation in VSMCs. Here, we found that CGRP could inhibit inflammation and decrease ADAM17 expression and activation of EGFR and ERK1/2 in VSMCs stimulated with Ang II. Results of siRNA demonstrated that ADAM17 siRNA attenuated Ang II-induced inflammation and up-regulation of activities of EGFR and ERK1/2 in VSMCs. Furthermore, the EGFR-ERK1/2 pathway promoted Ang II-induced VSMC inflammation. In summary, these findings identify the anti-inflammatory effect of CGRP in VSMCs stimulated by Ang II and suggest that ADAM17 is involved in the protective effect of CGRP against Ang II-induced inflammation via the EGFR-ERK1/2 pathway in VSMCs.